Porn video shows, local brew, and transactional sex: HIV risk among youth in Kisumu, Kenya - Voeten Helene ACM; Njue Carolyne; Remes Pieter (BMC, 2011)
Abstract Background Kisumu has shown a rising HIV prevalence over the past sentinel surveillance surveys, and most new infections are occurring among youth. We conducted a qualitative study to explore risk situations that can explain the high HIV prevalence among youth in Kisumu town, Kenya Methods We conducted in-depth interviews with 150 adolescents aged 15 to 20, held 4 focus group discussions, and made 48 observations at places where youth spend their free time. Results Porn video shows and local brew dens were identified as popular events where unprotected multipartner, concurrent, coerced and transactional sex occurs between adolescents. Video halls - rooms with a TV and VCR - often show pornography at night for a very small fee, and minors are allowed. Forced sex, gang rape and multiple concurrent relationships characterised the sexual encounters of youth, frequently facilitated by the abuse of alcohol, which is available for minors at low cost in local brew dens. For many sexually active girls, their vulnerability to STI/HIV infection is enhanced due to financial inequality, gender-related power difference and cultural norms. The desire for love and sexual pleasure also contributed to their multiple concurrent partnerships. A substantial number of girls and young women engaged in transactional sex, often with much older working partners. These partners had a stronger socio-economic position than young women, enabling them to use money/gifts as leverage for sex. Condom use was irregular during all types of sexual encounters. Conclusions In Kisumu, local brew dens and porn video halls facilitate risky sexual encounters between youth. These places should be regulated and monitored by the government. Our study strongly points to female vulnerabilities and the role of men in perpetuating the local epidemic. Young men should be targeted in prevention activities, to change their attitudes related to power and control in relationships. Girls should be empowered how to negotiate safe sex, and their poverty should be addressed through income-generating activities.